MNX (Medium Duration Nutrition and Resistance-Vibration Exercise) Bed-Rest: Effect of Resistance Vibration Exercise Alone or Combined With Whey Protein Supplementation on Cardiovascular System in 21-Day Head-Down Bed Rest - Guinet, Patrick; MacNamara, James Patrick; Berry, Matthieu; Larcher, Françoise; Bareille, Marie-Pierre; Custaud, Marc-Antoine; Pavy-Le Traon, Anne; Levine, Benjamin D.; Navasiolava, Nastassia (Frontiers in Physiology, 2020)
Current inflight countermeasures do not completely prevent bone and cardiovascular changes induced by microgravity. High load Resistance Exercise combined with whole body Vibration (RVE) demonstrated benefits on bone and cardiovascular system during previous Head Down Bed Rest (HDBR) studies. We examined the effectiveness of RVE alone or combined with a nutritional supplementation of Whey protein (NeX) on cardiovascular deconditioning. Eight male subjects (age 34 ± 8 year) in a crossover design completed three 21-day HDBR campaigns (Control-CON, RVE and NeX). Pre and post HDBR Orthostatic Tolerance (OT) was evaluated by a 15 minute head up tilt test followed by increasing levels of Lower Body Negative Pressure (LBNP). Heart rate, blood pressure and Sympathetic Index (ΣI) through spectral analysis were measured during OT test. Plasma Volume (PV), Maximal Oxygen Uptake (VO2max) were measured before and after each campaign. Left ventricular mass, left ventricular end diastolic (LVEDV), end systolic (LVESV), stroke (SV) volumes, and circumferential deformation at rest and during an orthostatic stress simulated by a 30 mmHg LBNP were measured by cardiac MRI. RVE failed to prevent any change in these variables and NeX did not have any additional effect over exercise alone. In the 3 groups, (1) OT time dropped similarly (bed rest p<0.001), (2) HR and ΣI were increased at rest at the end of HDBR and HR increased markedly during LBNP-tilt test, with inability to increase further the ΣI, (3) PV dropped (bed rest p<0.001), along with LVEDV, LVESV and SV (p=0.08, p<0.001, and p=0.045 respectively), (4) Left ventricle mass did not change significantly, (5) Deformation of the heart assessed by global circumferential strain was preserved and early diastolic circumferential strain rate was increased during orthostatic stress at the end of HDBR, illustrating preserved systolic and diastolic function respectively, without any difference between groups. Despite the drop in PV and LV volumes, RVE and NeX tended to alleviate the decrease in VO2max. In conclusion, RVE and NeX failed to prevent the cardiovascular deconditioning induced by a 21 day-HDBR.